Historical Topicality in Arnold Bennett and Edward Knoblock’s Milestones - Lukas Klik (Cahiers Victoriens et Edouardiens)
Arnold Bennett was one of the key figures of early twentieth century British literature. However, although literary criticism has engaged with his novels, his dramatic oeuvre remains a blind spot in scholarship. In this article, I want to lay out the subtleties of his play Milestones (1912), which he wrote in collaboration with Edward Knoblock. In particular, I show that the text is characterised by an intense interest in minute detail, which manifests itself through a high number of topical allusions to political, cultural and social issues. Moreover I also consider these references in the context of the aim of the playwrights in writing the play more generally. Here, I suggest that the topical allusions serve to underpin the play’s main point about the necessity to accept change, especially with regard to the role of women, by illustrating the inevitability of change. Through its interest in Bennett’s dramatic contributions, this article, then, seeks to complicate our understanding of British drama at the turn of the twentieth century.